2015
DOI: 10.1053/j.jrn.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Proteins and Calories Is Inversely Associated With The Oxidation State of Plasma Thiols in End-Stage Renal Disease Patients

Abstract: Background Oxidative stress contributes to the pathogenesis of protein-energy wasting (PEW) in maintenance hemodialysis (MHD) patients. It remains uncertain, however, whether and how food intake is involved in the causal relationship between oxidative stress and PEW. Methods 71 adult MHD Patients and 24 healthy subjects (Control) were studied cross-sectionally with analyses of diet record and of oxidative stress, as measured by a battery of plasma thiols including the protein sulfhydryl (-SH) group levels (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 45 publications
0
15
2
Order By: Relevance
“…reported that in patients with acute appendicitis dynamic thiol/disulfide homeostasis shifted towards disulfide formation due to thiol oxidation. The importance of thiol/disulfide homeostasis in many diseases, including chronic renal disease, severe coronary disease, migraine, obstructive sleep apnea, and pulmonary thromboembolism, has been reported . In the present study, although the thiol/disulfide ratio was slightly higher in the JIA patients than in the controls, the difference was not significant.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…reported that in patients with acute appendicitis dynamic thiol/disulfide homeostasis shifted towards disulfide formation due to thiol oxidation. The importance of thiol/disulfide homeostasis in many diseases, including chronic renal disease, severe coronary disease, migraine, obstructive sleep apnea, and pulmonary thromboembolism, has been reported . In the present study, although the thiol/disulfide ratio was slightly higher in the JIA patients than in the controls, the difference was not significant.…”
Section: Discussioncontrasting
confidence: 80%
“…The importance of thiol/disulfide homeostasis in many diseases, including chronic renal disease, severe coronary disease, migraine, obstructive sleep apnea, and pulmonary thromboembolism, has been reported. 5,6,[11][12][13][14] In the present study, although the thiol/disulfide ratio was slightly higher in the JIA patients than in the controls, the difference was not significant. The present small sample size may be why the present findings differ from those reported earlier by Altıparmak et al 6 In clinical practice CRP and ESR are used to predict the severity of inflammation in inflammatory disease.…”
Section: Discussioncontrasting
confidence: 78%
“…There are significant differences in total plasma protein and albumin concentrations between healthy subjects and patients with ESRD [23], [40], as well as for each ESRD patient before and after a single HD session [23]. The latter is due to ultrafiltration performed during the dialysis session in order to restore the dry body weight of the patient.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in haemodialyzed patients plasma protein oxidation is revealed by decreased P-SH [23], which might result from S -thiolation, the formation of mixed disulphides between P-SH and low-molecular-mass aminothiols, which is considered to be the mechanism protecting P-SH from losing their biological activity by irreversible oxidation [47], [48]. S -thiolated plasma proteins are indeed increased in haemodialyzed patients [21], [22], [23], [40]. However, a single HD session, by removing solutes responsible for increasing ROS production and the low-molecular-mass aminothiols involved in S -thiolation [21], caused transient return of plasma P-SH to the level equal or close to that occurring in healthy subjects [20], [21], [23].…”
Section: Discussionmentioning
confidence: 99%
“…Protein intake above the physiological need leads to the increase in the catabolic pathways of amino acids, increasing the production of by-products such as urea, adenosine triphosphate (ATP), carbon dioxide, glucose, acetyl coenzyme A, and ketone bodies. Some of these by-products can have adverse effects in the body [19].…”
Section: Resultsmentioning
confidence: 99%